Emergency hospitals for COVID-19 construction and operation manual - Yan, Zhi; Yan, Ge (World Scientific, 2020)
"The COVID-19 outbreak in Wuhan, Hubei, saw great numbers of patients overwhelming the admission capacity of designated infectious diseases hospitals, which in turn led to insufficient medical supplies fulfilling treatment needs. Hence, Zall Foundation proposed the construction of COVID-19 Emergency Hospitals to effectively respond to the surging number of COVID-19 cases. This involved the conversion of existing hospitals that have insufficient, or do not have admission capacities for infectious diseases patients, into emergency hospitals that solely focus on receiving suspected and confirmed COVID-19 cases. From January 30, 2020, Zall Foundation, along with professional medical institutions, reconstructed seven existing professional medical institutions into COVID-19 Emergency Hospitals in less than 10 days. In total, 4,583 wards were provided after renovation, where 2,833 confirmed and suspected COVID-19 patients were cured. The COVID-19 Emergency Hospitals have played an important role in China's epidemic prevention and control by efficiently easing the problems of insufficient ward beds and inadequate admission capacities of infectious diseases hospitals. Based on the experience of construction and operation of the emergency hospitals which are designed in strict adherence to relevant medical standards and regulations, this manual has been compiled by the Zall Foundation. It aims to provide useful reference to the reconstruction of existing hospitals and practice of expanding medical resources for all other regions around the world, to effectively contribute to pandemic control. The manual has been translated into more than 20 languages." --